Specificity of formation of the tax base on corporate income tax in construction (Journal of Economic Research & Business Administration, 2020)
The purpose of the study – reflects a study of the methodology of the process of determining the taxbase when calculating corporate income tax on (example of the construction company “XXX”). Identificationof the main problems in calculating income tax and advance payments.Originality / value – the basic aspects of the taxation process are noted. To clearly reflect the processof determining income tax as a research base, we analyzed data on the financial and tax reportingof a construction company. An example of determining income tax and calculating advance paymentsis given. Recommendations on tax accounting, including for construction companies, are developed,specific aspects of taxation in this industry are indicated.Conclusions – the need for improving the tax accounting methodology has been identified and suggestionshave been developed to achieve the goal of the study. The practical significance of the articlewill allow accounting and auditing services to take into account the main points in determining the taxbase and drawing up the tax accounting policy in terms of corporate income tax. Features of tax accountingin construction makes it possible to disclose the specifics of determining the tax base for corporateincome tax for Kazakhstan companies.